1974
DOI: 10.3181/00379727-146-38117
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Angiotensin Converting Enzyme Inhibition on Renal Autoregulation

Abstract: The mechanisms responsible for renal autoregulation continue to arouse considerable interest, and much of the present controversy is centered upon the role of the renin-angiotensin system in modulating the renal hemodynamic response to alterations in renal arterial pressure. Britton proposed a renin-renal autoregulation hypothesis which postulated that plasma angiotensinogen (renin substrate) and converting enzyme interact with cytoplasmic renin at the luminal surfact of the wall of the afferent arteriole to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

1975
1975
1992
1992

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 5 publications
(5 reference statements)
0
7
0
Order By: Relevance
“…There seems to be general agreement that RAS plays only a minor role in the autoregu lation of RBF [Johns, 1979], while reports have been conflicting with regard to the par ticipation of RAS in the regulation of GFR during changes in RAP [Gagnon et al, 1974;Hall et al, 1977].…”
Section: Discussionmentioning
confidence: 99%
“…There seems to be general agreement that RAS plays only a minor role in the autoregu lation of RBF [Johns, 1979], while reports have been conflicting with regard to the par ticipation of RAS in the regulation of GFR during changes in RAP [Gagnon et al, 1974;Hall et al, 1977].…”
Section: Discussionmentioning
confidence: 99%
“…Studies evaluating redistribution have shown differ ent results in different laboratories. In renindepleted dogs or during C E I, a reduction in RAP redistributed flow away from the outer cortex [10,26]. Other investigators have observed little or no changes in cortical flow distribution in normal and renin-depleted animals, when the R A P was lowered [27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…and urinary sodium excretion rates in dogs previously maintained on a sodi um-restricted diet [14,16]. In spite o f the increases in RBF, there was a well-main tained and highly efficient capability to autoregulate R B F in response to reductions in R A P [10][11][12][13][14], In fact, autoregulatory behavior was actually enhanced, since RBF was autoregulated with a high degree o f effi ciency down to RAP values lower than during control conditions; in some cases, there were increases in R BF at the lower values o f RAP. Also, the average G F R values shown in ta ble II indicate that there were no significant differences in G F R obtained at the four RAP ranges evaluated during the CEI period.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with the earlier findings observed with SQ20,881 administration in the cat (Johns, 1979) and those of Abe, Kishimoto & Yamamoto (1976), Anderson et al (1975), Kimbrough, Vaughan, Carey & Ayres (1977) in the dog and Arendshorst & Finn (1977) in the rat which suggest that under normal dietary sodium conditions renal blood flow is very little influenced by circulating angiotensin II. However, it is clear that in states where the plasma levels of angiotensin II are raised, such as following low dietary sodium (Gagnon, Rice & Flamenbaum, 1974;Kimbrough et al, 1977;Hall et al, 1977bHall et al, , 1979 or inferior vena caval constriction (Freeman, Davis, Vitale & Johnson, 1973) angiotensin II can greatly influence the rate of renal blood flow.…”
Section: Discussionmentioning
confidence: 99%